Translational Approaches to Autism Spectrum Disorder - Robinson-Agramonte, Maria de los Angeles; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book addresses and synthesizes recent basic, translational, and clinical research with the goal of understanding the mechanisms behind autism spectrum disorder (ASD) and how they lead to altered brain function and behavior. Bringing clarity to these mechanisms will lead to more effective therapies for the various heterogeneous pathologies that comprise ASD. Currently there are few, if any, proven therapies for the majority of the disorders. Topics addressed in this book include neural plasticity, neuroimmunology, neuroinflammation, neuroimaging, and appropriate animal and genetic models.
Autism: what is it -- Epidemiology of Autism Spectrum Disorders -- The Genetic Basis of Autism Spectrum Disorder -- Autism spectrum disorder: A clinical neurophysiology approach I -- Autism spectrum disorder: A clinical neurophysiology approach II -- Neuroimages in Autism -- Autism, development and neural plasticity -- Neuroinflammation in animal models of autism -- Understanding of neuroimmunology in autism spectrum disorder -- Antibody mediating autoimmune reaction in autism spectrum disorder -- Current therapies.
Keywords: Neurosciences; Neurology .; Neurosciences; Neurology